Integrasi Artificial Intelligence dalam Manajemen Modern: Peluang, Tantangan, dan Dampaknya di Era Transformasi Digital - Mohammad Abdul Aziz Alwahedi; Durrin Ni’am; Mohammad Firmansyah (Journal of Economics, Management, and Accounting, 2025)
This study examines the integration of intelligent technologies within modern management practices and highlights how digital transformation reshapes organizational structures and decision-making processes. Through a descriptive–qualitative approach supported by thematic synthesis of reputable scientific publications, international reports, and empirical findings from 2020–2025, this research identifies key opportunities, challenges, and managerial implications emerging from the adoption of advanced data-driven systems. The findings reveal that intelligent automation enhances managerial accuracy, operational efficiency, and strategic responsiveness by enabling real-time processing of organizational information. However, successful implementation depends heavily on employee readiness, structured governance, and the ability of leaders to develop strong analytical competencies. The study also notes that reliance on predictive systems requires continuous evaluation to minimize bias and ensure inclusive decision outcomes. Empirical evidence from global datasets further demonstrates the growing adoption of automated decision-making tools across various managerial functions. Overall, the research concludes that organizations capable of aligning technological capabilities with adaptive management strategies will strengthen their competitive advantage and improve long-term performance in the digital transformation era